2016
DOI: 10.1016/j.canrad.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility evaluation of prone breast irradiation with the Sagittilt© system including residual-intrafractional error assessment

Abstract: Please cite this article in press as: Lakosi F, et al. Feasibility evaluation of prone breast irradiation with the Sagittilt © system including residual-intrafractional error assessment. Cancer Radiother (2016), http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…While Joszef et al 28 report slightly superior margins along the LL and CC axis compared to the prone crawl setup, their report only concerns partial breast irradiation, so effects of edema on patient shift might not be as pronounced. In general, our crawl couch results compare favourably to most of the results published for prone radiotherapy [13][14][15]18,22,[26][27][28][29][30] , especially for the AP and LL systematic error distribution defined by M and ∑. Because our random error σ is lower than in these other studies, we can obtain smaller PTV margins of around 1 cm in these directions.…”
Section: Discussionsupporting
confidence: 84%
“…While Joszef et al 28 report slightly superior margins along the LL and CC axis compared to the prone crawl setup, their report only concerns partial breast irradiation, so effects of edema on patient shift might not be as pronounced. In general, our crawl couch results compare favourably to most of the results published for prone radiotherapy [13][14][15]18,22,[26][27][28][29][30] , especially for the AP and LL systematic error distribution defined by M and ∑. Because our random error σ is lower than in these other studies, we can obtain smaller PTV margins of around 1 cm in these directions.…”
Section: Discussionsupporting
confidence: 84%
“…Another study by Lakosi et al . 17 used CBCT to study the setup errors of 36 cases of breast cancer in the prone position. Their results showed that Σ and δ were about 4.5 mm and 5.4 mm in left-right, 3.9 mm and 3.8 mm in cranial-caudal, 3.3 mm and 2.8 mm in anterior-posterior direction, the PTV margins were 15.0 mm, 12.3 mm and 10.3 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The supine and prone CT series and supine topogram of patients included in the study ''Individualized positioning for maximum heart and index breast protection during breast irradiation: comparative study between Prone and Supine (Approval: 26/09/2013, B707201318246) were retrospectively used for independent testing. The protocol of patient positioning, delineation and radiation treatment planning has been described [27].…”
Section: External Testingmentioning
confidence: 99%
“…Interfractional differences may be especially large in the prone position [18,30]. Lakosi et al found population systematic error values of 4.5/3.9/3.3 mm in the lateral/longitudinal/vertical directions, while the random error was 5.4/3.8/2.8 mm [27]. Among our recent breast radiotherapy cases, the population systematic and random error in the lateral/longitudinal/vertical directions was similar in the prone position vs. supine position (3.4/2.3/2.7 mm and 7.8/4.6/6.9 mm, respectively vs. 2.2/3.0/1.6 mm and 6.7/5.5/4.5 mm, respectively).…”
Section: Gyheartmentioning
confidence: 99%